Using Schur rings to find the automorphism group of Cayley graph of order where are prime numbers - Ali, Eskander; Hassoon, Ahed (Latakia University Journal -Basic Sciences Series, 2018)
In this paper we determine the automorphism group of Cayley graph over the group where are prime numbers, by building the corresponding Schur ring which is generated by , and determine the automorphism group of this ring which is the automorphism group of this graph